Aplikasi Toontastic: Perancangan Media Pembelajaran untuk Mengembangkan Nilai Karakter Smart Entrepreneur Anak Usia Dini: Indonesia - Westhisi, Sharina Munggaraning; Ririn Hunafa Lestari; Liza Bunga Aprilia (P2M STKIP Siliwangi, 2024)
The study aims to explain the design of digital learning media using the Toontastic application in developing the character values of Early Childhood, for example the character value of smart entrepreneur. This study used a qualitative method involving 30 students (pre-service teachers of Early Childhood Education (ECE)). Data collected through interviews and study documentation were analyzed descriptively. Data obtained from interviews were analyzed using thematic analysis with two themes consisting of designing learning media through Toontastic application and the other theme is the development of smart entrepreneur character values of early childhood. The results showed that the aspects of designing learning media for early childhood through Toontastic application consisted of content, appearance, time, and value. In addition, this media can contribute to the development of smart entrepreneur character values of early childhood to face global challenges in the future. Then, this result can invite ECE educators, parents, and the community to develop the character values of smart entrepreneur of early childhood through other applications as a form of technology utilization in education.